The sessions [videorecording (DVD)]. - Lewin, Ben; Hawkes, John, 1959-; Hunt, Helen, 1963-; Macy, William H., 1950-; Bloodgood, Moon (20th Century Fox Home Entertainment, 2013)
Paralyzed and confined to an iron lung since childhood, poet-journalist Mark O'Brien has overcome adversity time and time again. But now, at age 38, he faces his toughest challenge yet: losing his virginity. With the help of a beautiful therapist, a sympathetic priest, and his own unbridled sense of optimism and humor, Mark embarks on an extraordinary personal journey to discover the wondrous pleasures that make life worth living.